WEIGHTED SPACES OF FUNCTIONS HARMONIC IN THE UNIT BALL - Petrosyan, A.I.; Avetisyan, K.I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
We introduce the Banach spaces h_∞(φ), h_0(φ) and h^1(ψ) functions harmonic in the unit ball BR^n. These spaces depend on weight functions φ, ψ. We prove that if φ and ψ form a normal pair, then h^1(ψ)^*h_∞(φ) and h_0(φ)^*h^1(ψ).